Estilos de Apego y adicción al Facebook en estudiantes de segundo año de bachillerato de la unidad educativa “Pedro Vicente Maldonado” Riobamba, periodo Diciembre 2015-Mayo 2016. - Muñoz Inguillay, Silvia Alexandra (2016)
This research work analyzes the styles of attachment and addiction to Facebook in the students of second year of Bachelor at "Pedro Vicente Maldonado" high school Riobamba, period December 2015 - May 2016, the objective was to analyze the styles of attachment and addiction to Facebook. The sample were 162 students that was obtained by criteria of inclusion and exclusion. The instrument that is used to identify those styles of attachment is the attachment´s questionnaire CaMir-R that evaluates them styles of attachment in adolescents of way collective; for measuring the addition to the facebook social networking inventory (UPAO), was applied which evaluates and identifies the areas and levels of addiction is used for the measurement of the Facebook addiction. The scientific methods, a non-experimental design, transverse descriptive type was used. Through the analysis and interpretation of the test is shown that 85.8% of students presents an Avoidant insecure attachment; areas and levels of addiction, high level is obtained by referring to two of the four areas, unwillingness with 46% and need to assertion whit 48%, showing a lack of strength to control its desire to stay linked social network, lack of self-confidence, evasion mechanisms to family conflicts and seeking an affiliation with others through social networks. In the list of variables it concluded that attachment styles directly influence addiction Facebook. Distraction techniques, control and programming of activities, stop thinking and relaxation training aimed at students: After having checked the existing problems of psychological intervention strategies are proposed.